Changing the playbook : how power, profit, and politics transformed college sports - Chudacoff, Howard P. (UPCC book collections on Project MUSE. History., 2015)
"One of the great attractions of American sports is the speed with which they move. Another is that every championship season will hold their banners and trophies in places of honor. And still another is that every bad season comes to an end and hope springs eternal that next year will be splendid. Amid all the swiftly changing seasons of sports, and amid the moments that are remembered, even savored, there have been events and decisions that have proved to be turning points. Focusing on the period after 1950, Howard Chudacoff identifies seven such turning points. They are: (1)The emerging role of the NCAA in organizing sports, establishing rules, and enforcing them; (2)The integration of colleges and universities; (3)Contracts offered for college football for the new technology, TV; (4)The Supreme Court decision of 1984 that settled who could control TV revenue; (5)The passage of Title IX in 1972, requiring colleges and universities to expand women's varsity athletics; (6)The widespread scandals involving cheating in games, eligibility, and recruitment; and (7)Payment to players. Chudacoff provides the histories of each, all of which were controversial. Some still are"--